Evaluasi Kejelasan Bahasa Indonesia dalam Informasi Harga dan Layanan pada Objek Wisata Benteng Otanaha - Meilina Widya Dali; Nabil Albani Rayid; Desy Divarianti Lagona; Dwi Putri Ramadhani Urusi; Balgis Potutu; Abdul Rahmat Igirisa; Moh. Ripal R. Adam; Najwa Ramadhani Dunggio; Nayla Azahra Ali; Novaldi Hidayat F. Lolong; Nur Indah Hiola; Putri Wahyuni Ntai; Risya Agustina; Sri Maharani I. Yado; Siti Nurazizah Suleman (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to evaluate the clarity of the use of the Indonesian language in conveying information on entrance ticket prices at the Benteng Otanaha tourist attraction as a form of public accountability. The problem underlying this research is the inconsistency in the application of entrance ticket prices for visitors, particularly for group visitors, where some groups are charged lower prices while others are charged the normal rate without clear explanations. This research employs a qualitative descriptive method with data collection techniques including direct observation at the tourist site and in-depth interviews with site attendants. The results indicate that the absence of clear written information regarding ticket pricing regulations leads to differences in verbal explanations provided by the staff. This condition has the potential to cause confusion in visitors’ perceptions due to perceived unfairness in the determination of entrance fees at the tourist attraction. From an accounting perspective, this situation reflects that public accountability in the disclosure of pricing information has not been optimally implemented. Therefore, it is necessary to present clear, consistent, and standardized pricing information using proper Indonesian language to enhance transparency and public trust in the management of the tourist attraction.